1972
DOI: 10.1029/jb077i020p03796
|View full text |Cite
|
Sign up to set email alerts
|

Cohesive force across the tip of a longitudinal-shear crack and Griffith's specific surface energy

Abstract: The cohesive force across the fault plane is considered in order to understand the physical mechanism of rupture at the tip of a longitudinal-shear crack. The elastic field around the tip of a crack and the condition of rupture growth are systematically derived from the assumption that the cohesive force is given as a function of the displacement discontinuity. This assumption is more physically meaningful than those originally used by G.I. Barenblatt in 1959 and 1962. The stress field around the tip is calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
646
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 870 publications
(659 citation statements)
references
References 11 publications
11
646
0
2
Order By: Relevance
“…This is a transitional process from static to dynamic friction. Such weakening has been predicted theoretically (e.g., Ida 1972;Palmer and Rice 1973) and confirmed in the laboratory (e.g., Dieterich 1978;Ohnaka et al 1987;Tsutsumi and Shimamoto 1997).…”
Section: Slip-weakening Distancementioning
confidence: 85%
“…This is a transitional process from static to dynamic friction. Such weakening has been predicted theoretically (e.g., Ida 1972;Palmer and Rice 1973) and confirmed in the laboratory (e.g., Dieterich 1978;Ohnaka et al 1987;Tsutsumi and Shimamoto 1997).…”
Section: Slip-weakening Distancementioning
confidence: 85%
“…That information will allow us to compute the spatio-temporal evolution of the apparent stress in the fault plane. [Ida, 1972] …”
Section: Crap(t) = 107rp/•a Mo(t) ----107rp• 3 Fo T/•/(t) (3)mentioning
confidence: 99%
“…The equation of motion is solved in an elastic body with a criterion for stress drop on the fault. Assumptions such as a constant rupture velocity or a linear slip-weakening law [Ida, 1972] have been successfully used as criteria for stress drop [e.g., Madariaga, 1976;Mikumo and Miyatake, 1978;Day, 1982]. The studies showed certain relations between the distribution of initial shear stress, slip velocity, amount of slip, and rupture propagation velocity, as well as the characteristics of elastic wave radiation.…”
Section: Introductionmentioning
confidence: 99%